The prekernel of cooperative games with alpha-excess - Xia Zhang; René van den Brink; Arantza Estévez-Fernández (Tinbergen Institute, 2021)
In this paper, we introduce a new approach to measure the dissatisfaction for coalitions of players in cooperative transferable utility games. This is done by considering affine (and convex) combinations of the classical excess and the proportional excess. Based on this so-called alpha-excess, we define new solution concepts for cooperative games, such as the alpha-prenucleolus and the alpha-prekernel. The classical prenucleolus and prekernel are a special case. We characterize the alpha-prekernel by strong stability and the alpha-balanced surplus property. Also, we show that the payoff vector generated by the alpha-prenucleolus belongs to the alpha-prekernel.
Keywords: 330; Alpha-excess; Alpha-prenucleolus; Alpha-prekernel; Alpha-balanced surplus